The Role of the 2019-2021 International Balance of Payments for Indonesia Economic Balance - Tuahna Sari Nasution; Selva Anzara Putri Harahap; Ela Kumala Sari Hasibuan; Khairani Matondang (Indonesian Journal of Advanced Research, 2023)
The international balance of payments plays an important role as an indicator of a country's economic fundamentals. The international balance of payments is used as the basis for making policies or regulations related to various matters related to international trade. This study aims to analyze the Role of the 2019-2021 International Balance of Payments for Indonesia's Economic Balance which is studied using a descriptive method with a quantitative approach. The data used is time series data, time series data is annual data for 3 years, namely from 2019 to 2021. The results show that the international balance of payments in 2019-2021 for the balance of the Indonesian economy can be explained by these two methods which are shown with data released by BPS (Central Bureau of Statistics).